Стратегічні перспективи розвитку Азійсько-Тихоокеанського регіону - Белінська, Яніна Василівна; Бобровник, Вікторія Миколаївна; Белінська, Яніна (Видавничий дім «Гельветика», 2021)
У статті досліджено процес та причини формування Азійсько-Тихоокеанського регіону як нового глобального геополітичного лідера, висвітлено основні аспекти сучасного становища країн Азійсько-Тихоокеанського регіону у світі. У роботі висвітлено вплив політики США на геополітичну трансформацію країн Азійсько-Тихоокеанського регіону, а також визначено основні інтереси Сполучених Штатів у цьому регіоні. У сучасному глобалізованому світі Азіатсько-Тихоокеанський регіон (АТР) став зоною негайного динамічного економічного розвитку. Насправді в Азії та Тихоокеанському регіоні змінюються економічні та політичні можливості, на які припадає близько половини світового промислового виробництва та світової торгівлі. У роботі висвітлено основні стратегічні перспективи розвитку Азійсько-тихоокеанського регіону та найбільш вірогідних геополітичних сценарії розвитку подій вданому регіоні

The article examines the process and reasons for the formation of the Asia-Pacific region as a new global geopolitical leader, highlighting the main aspects of the current situation in the Asia-Pacific region in the world. The articles highlight the impact of US policy on the geopolitical transformation of the Asia-Pacific region, as well as identify the main US interests in this region. The Asia-Pacific region is a promising and dynamic region in the world. Significant differences in the economic, political and social spheres do not affect the countries of the Asia-Pacific region, which actively interact with each other. In today's globalized world, the Asia-Pacific region (APR) has become a zone of negative dynamic economic development. In fact, economic and political opportunities are changing in Asia and the Pacific, joining half of world industrial production and world trade. Outpacing other regions of the world for growth, the Asia-Pacific region creates the preconditions for considering international economic integration as a process that promotes the development and growth of consumption and production. Therefore, the main trends of regional development are analyzed in the articles. The articles present the main problems in relations between the states of the region and with territorial issues, due to, despite the dynamic economic cooperation, the socio-political situation in the Asia-Pacific region, identified by contradictory processes of overload in the post-Cold War period. countries in the region that ensure economic interests and multilateral cooperation at the forefront of their strategies. The articles highlight the main strategic prospects for the development of the Asia-Pacific region and the greater likelihood of geopolitical development scenarios developing in this region. Thus, the development of political and economic processes in the Asia-Pacific region is determined by the increasing role of China and India, Russia's efforts to increase its influence on the redistribution of power in the regions and the relative decline of US activities in the region
Keywords: стратегія; Азійсько-Тихоокеанський регіон; США; розвиток; Китай; strategy; Asia-Pacific region; USA; development; China